School governance : policy, politics and practices - Baxter, Jacqueline (Bristol : Policy Press, 2017)
Taking the Trojan Horse Affair as a starting point, this book examines what questions the affair raised for the governing of education in England and what implications this has for the new government. By examining the political, social and economic contexts surrounding education in 2015, the book explores the politics surrounding school governance and examines the pressures and challenges engendered by the current system and what they may mean for the future of the governance of education in this country.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 14, 2016).
Keywords: School management and organization -- England; Education and state -- England; Educational leadership -- England; Islam and civil society -- Great Britain; Education